(untitled) (CIPEEX, 2025)
Trichuriasis is a parasitic infection caused by the nematode Trichuris trichiura. It is the third most common geohelminth worldwide, prevalent in tropical and subtropical regions. In Brazil, it particularly affects children and adolescents in the North and Northeast regions, where basic sanitation is limited. Transmission occurs via the fecal-oral route through the consumption of contaminated food or water. The parasite’s eggs hatch in the small intestine, and larvae migrate to the large intestine, where they mature into adult worms capable of releasing eggs in feces. Adult worms can live for one to two years in the human body and are characterized by their whip-like shape. Severe infections can result in abdominal pain, anorexia, diarrhea, weight loss, anemia, and rectal prolapse, especially in children. Treatment typically includes benzimidazole compounds like albendazole, mebendazole, and ivermectin. Low income, poor hygiene, and inadequate sanitation are critical factors in the spread of this parasitosis. Improving socio-epidemiological conditions directly reduces the incidence of whipworm, enhancing the quality of life for affected populations.